중국 비대면 및 대면 자동차 보험 시장의 서비스 품질 공통모델 개발 연구 - 곽영식; Kwak Young Sik; 한강일; Han Kang-il; 구자경; Koo Ja Kyung; 홍재원; Hong Jae Won; 남윤정; Nam Yoon Jung; 박지영; Pak Ji Young (品質經營學會誌, 2022)
Purpose: This study aims to develop a communality model to measure the service quality that the customers encounter on face-to-face and non-face-to-face automobile insurance before and after insurance purchase. Methods: For these purposes, we conduct a five-step program to develop a comprehensive communality model to measure service quality except insurance purchase channels. Results: As a result, we find five communality factors: value-added service for automobile maintenance, value- added service for drivers, quickness, dispatch service, and convenience of the service process. And the relative importance of service quality factors was in the order of value-added service for drivers, the convenience of the service process, quickness, and dispatch service, respectively. Conclusion: This study developed the opportunities to enhance service quality to attract customers. And it contributes to the academic literature by reporting the industry-specific service quality model, which maintains a theoretical gap in the online and offline automobile insurance industry.